Geographical statistics in Brazil: a kaleidoscope of the categories of territories - Chatel, Cathy; Beltrao Sposito, Maria Encarnacao [UNESP] (Revues Org, 2019)
The Brazilian Institute of Geography and Statistics (IBGE) is, with INEGI in Mexico are the only ones in the world to claim the geography. But is it a scientific guarantee for researchers who implement local census data? The large number of territorial categories of official statistics of present-day Brazil reveals a great wealth of data, provided they are not considered as a turnkey material for research. From a pre-statistical European model inherited from the colonial period, to the rationality of the state, then to the liberal and post-modern context that spread in the globalized world, the IBGE categories reveal the paradoxes due to the superposition of different points of view on how to characterize the urban space. This translates into difficulties in understanding and using aggregated population data on official spatial and urban categories. The avatars of the current situation are symptomatic of the paradigm of complexity that increasingly influences the quantitative approach in the social sciences and more generally reflects a break between citizens, policies and the logic of experts. Based on an in-depth analysis of territorial categories produced by the IBGE, the article uses these sources to understand the criteria that prevail in the divisions of space and in the definition of the urban space by the institution in order to assess the interest and limitations of using these sources of information. This analysis should allow a better understanding and better use of the rich dataset spread by the national statistical services.
Keywords: population census; public statistic; territorial categories